Smoking determinants by gender: a pilot study in schools of the Viseu district - Precioso, José (2009)
According to the data of the Health Behaviour in School – Aged Children: 11 – 15 years old (HBSC), of 1997/ 98 and 2002, the smoking epidemic is growing in Portugal, particularly among the female adolescents. It seems to indicate that the preventive actions in our country are not working out, which can be an outcome of not considering important issues like gender differences. Much has been researched on the determinants of smoking but the existed data has not been conclusive or specific of Portugal. An Investigation Project is ongoing, aiming to deepen the knowledge of the adolescents’ determinants of smoking by gender and to develop more effective preventive actions. Preliminary results of the Project are here presented.